2020
DOI: 10.1111/jam.14609
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biofilms in nature: unlocking their potential for agricultural applications

Abstract: Soil environments are dynamic and the plant rhizosphere harbours a phenomenal diversity of micro-organisms which exchange signals and beneficial nutrients. Bipartite beneficial or symbiotic interactions with host roots, such as mycorrhizae and various bacteria, are relatively well characterized. In addition, a tripartite interaction also exists between plant roots, arbuscular mycorrhizal fungi (AMF) and associated bacteria. Bacterial biofilms exist as a sheet of bacterial cells in association with AMF structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 89 publications
3
60
0
Order By: Relevance
“…An important trait of plant-associated bacteria is the ability to colonize plant roots to facilitate, e.g., the exchange of metabolites ( Kloepper and Beauchamp, 1992 ; Pandit et al, 2020 ). For successful root colonization it can be beneficial for the bacteria to be able to produce biofilms ( Pandit et al, 2020 ), which was demonstrated for RL1, djl6, and BG43. Accordingly, the RL1 genome harbors genes encoding for enzymes involved in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…An important trait of plant-associated bacteria is the ability to colonize plant roots to facilitate, e.g., the exchange of metabolites ( Kloepper and Beauchamp, 1992 ; Pandit et al, 2020 ). For successful root colonization it can be beneficial for the bacteria to be able to produce biofilms ( Pandit et al, 2020 ), which was demonstrated for RL1, djl6, and BG43. Accordingly, the RL1 genome harbors genes encoding for enzymes involved in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial biofilms are ubiquitous in natural and engineered contexts, spanning plant roots to chronic human infections to anaerobic digestors (Hall-Stoodley et al, 2004;Pandit et al, 2020). As biofilms develop, metabolic stratification occurs, driven by steep concentration gradients of substrates, such as oxygen, that are consumed by cells at the biofilm periphery faster than the substrates can diffuse into the biofilm interior (Stewart 2003;Stewart and Franklin, 2008;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An important factor in soil stabilization and aggregation is the ability to excrete extracellular polymeric substances (EPS) mainly containing polysaccharides, proteins and nucleic acids (22,23). In addition to their physical property of acting as a glue binding soil particles, cell attachment and biofilm formation, these polymers provide crucial functions for microbes such as protection against drought, antibiotics and heavy metals, entrapment of nutrients and carbon storage, signaling, genetic exchange, adhesion and aggregation (6).…”
Section: Introductionmentioning
confidence: 99%